Motivasi Keluarga Dalam Memberikan Dukungan pada Pasien ODGJ dengan Malaria di Wilayah Puskesmas Arso Kota Kabupaten Keerom Provinsi Papua - Suriyani, Suriyani; Halim, Nasrah; Gentindatu, Sofietje J; Musphita, Fitri Dia (NHM PRESS, 2023)
One of the complications of malaria is cerebral malaria which causes mental disorders. The aim of this research is to determine the relationship between family motivation factors in providing support to ODGJ patients with malaria in the Arso City area, Keerom Regency. Research Method with a cross-sectional design. The population is all families who have ODGJ patients with a history of malaria, people who are declared clinical malaria and are registered as patients in Keerom Regency totaling 289 people. The sampling technique was simple random sampling and 51 people were obtained. However, at the time of data collection there were only 18 families, because some were unwilling and some had moved to the city. Data analysis used the Spearman's Rho statistical test. The results of research on strong family motivation, mostly good family support, amounted to 16 people (88.9%). This research also shows that the results of the Spearman's Rho statistical test obtained a p value of 0.002 (p<0.05) and a correlation coefficient value of r = 0.686. Conclusion: Family motivation factors are related to family support in providing support to ODGJ patients with malaria.